1978
DOI: 10.1172/jci109082
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Cell-Mediated Immunity in Hodgkin's Disease Mediated by Suppressor Lymphocytes and Monocytes

Abstract: A B S T R A C T In Hodgkin's disease a possible mechanism for impaired cellular immunity is cell-mediated suppression, defined as the inhibitory interaction between suppressor cells and effector lymphocytes. To test for the presence of suppressor cells in peripheral blood, we have modified the standard, one-way mixed lymphocyte culture by adding mitomycin C-treated mononuclear cells from the responder. Suppression, expressed as a percent of the base-line mixed lymphocyte culture in which these extra cells are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
29
0
1

Year Published

1980
1980
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(32 citation statements)
references
References 28 publications
2
29
0
1
Order By: Relevance
“…ABVD, various hybrid or alternative regimens) as well. The major reasons are infections resulting not only from neutropenia that is usually less pronounced during standard therapy, but also from the immunodeficiency of HL patients 6 . Thus, the relative dose intensity (RDI) of primary chemotherapy can be reduced in a significant proportion of patients, even those in the early stage of disease and treated with less intensive protocols.…”
Section: Introductionmentioning
confidence: 99%
“…ABVD, various hybrid or alternative regimens) as well. The major reasons are infections resulting not only from neutropenia that is usually less pronounced during standard therapy, but also from the immunodeficiency of HL patients 6 . Thus, the relative dose intensity (RDI) of primary chemotherapy can be reduced in a significant proportion of patients, even those in the early stage of disease and treated with less intensive protocols.…”
Section: Introductionmentioning
confidence: 99%
“…Suppression by a monocytoid cell contributes to the proliferative hyporesponsiveness of lymphocytes from patients with Hodgkin's disease (16)(17)(18)(19). This abnormality is associated with an increase in the number of monocytes relative to lymphocytes in monioniuclear leukocyte (MNL)1 preparations (17).…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that monocytes release excessive amounits of prostaglandins, thereby causing suppression (20). A second form of suppression, spontaneously effected by T lymphocytes, has been described with Hodgkini's disease (19,21).…”
Section: Introductionmentioning
confidence: 99%
“…Two of the 3 patients with the highest 51Cr release/103 NSE+ cells (Figure) were in a clinically inactive state of the disease. In contrast, a correlation has been reported between enhanced monocyte suppressor cells and disease activity (Hillinger & Herzig, 1978).…”
mentioning
confidence: 92%
“…Urbanitz et al (1975) found reduced phagocytosis in patients with advanced HD and Leb & Merritt (1978) described decreased monocyte chemotactic response and monocyte bactericidal activity in that disorder. Recently, monocyte suppressor function was found to be significantly higher in HD, possibly impairing cellular immunity (Hillinger & Herzig, 1978).…”
mentioning
confidence: 99%